The Role of Swadhar Greh Centers of Karnataka in Protecting Women - Srinivasa B.S., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The status of women in India is highly influenced by the patriarchal society. Women in general are the easy victims of domestic violence, discrimination, caste based atrocities in many situations across communities in India. As repercussions to family/ individual /societal conflicts Women are subjected to heinous crimes such as violence, murder, eve teasing, Kidnapping, rape etc. According to National Crime Records Bureau 2020; -A total of 3,71,503 cases of crime against women were registered during 2020. The crime rate recorded per lakh women population is 56.5 in 2020 compared to 62.3 in 2019.Considering the crime rates against women in India, the Government of India has taken up measures to reduce and prevent atrocities against women through strict judiciary measures. Further by considering the effect of crime on the victim, the central government has taken up remedial and protective measures towards women who are in distress. One such measures include the Swadhar Greh Scheme. This yojana/scheme addresses to those women in distress especially due to marital violence, societal crimes, etc. by providing immediate psychological and social support through short stay shelter homes that includes free medical and judicial support along with rehabilitative measures in order to bring them back to the mainstream society.
Keywords: Remedial; Rehabilitation; Mainstream; Empowerment; Self-reliance; Domestic violence; Distress